Fisetin Mitigates Chronic Lung Injury Induced by Benzo(a)Pyrene by Regulation of Inflammation and Oxidative Stress - Wanian M. Alwanian (Current Issues in Molecular Biology)
Background: Polycyclic aromatic hydrocarbons such as Benzo(a)Pyrene, which are produced by smoking or present in air pollution, greatly contribute to lung diseases. B(a)P has been found to induce inflammation and eventually lung cancer. Fisetin, a polyphenol, abundant in many fruits and vegetables, has an appealing therapeutic potential in many disorders, including inflammation and cancer. Objectives: This study aimed to investigate the importance of fisetin in the regulation of chronic lung inflammation and oxidative stress resulting from exposure to Benzo(a)Pyrene. Methods: The effect of fisetin on rats at a concentration of 50 mg/kg was evaluated by ELISA to measure oxidative stress and inflammatory markers. The tissue architecture was also investigated using hematoxylin and eosin (H&E) staining. The expression pattern of IL-6 in lung tissues was assayed using immunohistochemistry. Fibrosis was evaluated in lung tissues using Masson Trischrome and Sirius red stains. Cell apoptosis in lung tissues was studied using a TUNEL assay. Results: After exposure to Benzo(a)Pyrene for eight weeks, the data indicated that fisetin led to a significant reduction in oxidative stress, evidenced by the reduction of SOD, MDA, NO, GPH, and GPx. Moreover, IL-6, TNF-α, and CRP levels were also decreased, indicating a reduction in inflammation. Apoptosis was reduced upon fisetin treatment. Furthermore, a significant decrease in fibrosis was also observed. Conclusions: This study reveals the importance of fisetin as a natural product in the management of chronic lung injury by protecting lung tissues from inflammation, and its use suggests better prognosis in diseases caused by exposure to B(a)P.